Estimated exposure to EU regulated mycotoxins and risk characterization of aflatoxin-induced hepatic toxicity through the consumption of the toasted cereal flour called "gofio", a traditional food of the Canary Islands (Spain). (July 2016) - Luzardo, Octavio P.; Bernal-Suárez, María del Mar; Camacho, María; Henríquez-Hernández, Luis Alberto; Boada, Luis D.; Rial-Berriel, Cristian; Almeida-González, Maira; Zumbado, Manuel; Díaz-Díaz, Ricardo
Abstract: "Gofio" is a type of flour made from toasted grain, which is part of the staple food in the Canary Islands, Spain, in which the occurrence of Aflatoxins B1, B2, G1 and G2 (AFB1, AFB2, AFG1, AFG2), Fumonisins B1 and B2 (FB1 and FB2) Ochratoxin A (OTA), Deoxynivalenol (DNV) and Zearalenone (ZEA) was evaluated. 83% of the samples were contaminated with at least one mycotoxin and 69.2% of the analyzed samples showed co-occurrence of mycotoxins (range 2 to 8). All the concentrations were well below the established limits (maximum values of AFs = 0.42 μg/kg; FBs = 178.3 μg/kg; OTA = 0.3 μg/kg; DON = 92.5 μg/kg; and ZEA = 9.9 μg/kg). The daily dietary exposure to total AFs was estimated to be 7.1% of the TDI. This value was almost double in children, and considering the upper-bound approach could reach 35% of the TDI. For the rest of mycotoxins, the consumers would be exposed to less than 2% of their TDIs. The risk characterization indicates that there is a potential risk in developing aflatoxin induced liver cancer due to gofio consumption in the subpopulation which is simultaneously exposed to other hepatocarcinogens, such as the hepatitis B virus. Graphical abstract: Highlights: Survey of regulated mycotoxin in a traditional staple of the Canary Islands. All mycotoxins were below the EU MRLs. The estimated daily intake was low, except in the case of aflatoxins. The intake of aflatoxins through gofio would pose risk for HBsAg + population.